THE PUNK COMMUNITY'S RECEPTION OF SELF-CONCEPT PORTRAYALS IN THE MEDIA - salsabila, Nilna fassya; Akbar, Moh. Rifaldi (Acta Diurna: Jurnal Ilmu Komunikasi, 2024)
The problem is punk kids are always considered negative and underestimated by society. This study aims to find out how punk children perceive their self-concept in media. The method used is a qualitative method with a descriptive type. The data sources obtained by researchers used data collection, such as interviews with punk child informants, observation and documentation. The results of the study found that there were several factors for punk children, namely from family factors and friendship factors. This punk kid always gets negative comments about him. However, all the punk kids did was stay silent and didn't care about what was being commented on. This punk kid perceives his self-concept image in online media with its pros and cons. Punk kids see their self-concept as negative because there are people who wear punk-worthy attributes or appearances, but these people don't know what punk really means and often commit crimes. Therefore, punk is always labeled negatively even though it is not punk who does it. And also punk kids who think positively because one of the punk kids has seen his self-concept in a movie and in that movie he has high solidarity with social concerns.